The British Report upon Real Wages in America and England - Mitchell, Wesley C. (Quarterly Journal of Economics, 1911)
Journal Article The British Report Upon Real Wages in America and England Get access Wesley C. Mitchell Wesley C. Mitchell University of California Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 26, Issue 1, November 1911, Pages 160–163, https://doi.org/10.2307/1884530 Published: 01 November 1911